Kalkitoxin reduces osteoclast formation and resorption and protects against inflammatory bone loss - Li, Liang; Yang, Ming; Shrestha, Saroj Kumar; Kim, Hyoungsu; Gerwick, William H.; Soh, Yunjo (International Journal of Molecular Sciences, 2021)
Osteoclasts, bone-specified multinucleated cells produced by monocyte/macrophage, are involved in numerous bone destructive diseases such as arthritis, osteoporosis, and inflamma-tion-induced bone loss. The osteoclast differentiation mechanism suggests a possible strategy to treat bone diseases. In this regard, we recently examined the in vivo impact of kalkitoxin (KT), a marine product obtained from the marine cyanobacterium Moorena producens (previously Lyngbya majuscula), on the macrophage colony-stimulating factor (M-CSF) and on the receptor activator of nuclear factor κB ligand (RANKL)-stimulated in vitro osteoclastogenesis and inflamma-tion-mediated bone loss. We have now examined the molecular mechanism of KT in greater detail. KT decreased RANKL-induced bone marrow-derived macrophages (BMMs) tartrate-resistant acid phosphatase (TRAP)-multinucleated cells at a late stage. Likewise, KT suppressed RANKL-induced pit area and actin ring formation in BMM cells. Additionally, KT inhibited several RANKL-induced genes such as cathepsin K, matrix metalloproteinase (MMP-9), TRAP, and dendritic cell-specific transmembrane protein (DC-STAMP). In line with these results, RANKL stimulated both genes and protein expression of c-Fos and nuclear factor of activated T cells (NFATc1), and this was also suppressed by KT. Moreover, KT markedly decreased RANKL-induced p-ERK1/2 and p-JNK pathways at different time points. As a result, KT prevented inflammatory bone loss in mice, such as bone mineral density (BMD) and osteoclast differentiation markers. These experiments demonstrated that KT markedly inhibited osteoclast formation and inflammatory bone loss through NFATc1 and mitogen-activated protein kinase (MAPK) signaling pathways. Therefore, KT may have potential as a treatment for destructive bone diseases.
Keywords: Actins; Animals; Bone Density; Bone Resorption; Cathepsin K; Cell Survival; Inflammation; Janus Kinases; Lipids; Lipopolysaccharides; Lyngbya; Macrophage Colony-Stimulating Factor; Macrophages; Male; MAP Kinase Signaling System; Matrix Metalloproteinase 9; Membrane Proteins; Mice; Mice, Inbred ICR; Nerve Tissue Proteins; NFATC Transcription Factors; Osteoclasts; Osteogenesis; Phosphorylation; Proto-Oncogene Proteins c-fos; RANK Ligand; Tartrate-Resistant Acid Phosphatase; Thiazoles; Bone loss; Inflammation; Kalkitoxin; Marine natural product; Osteoclast